HUBUNGAN DISLIPIDEMIA DAN DIABETES MELITUS TIPE 2 DITINJAU DARI KOLESTEROL & TRIGLISERIDA DI RSDI BANJARBARU : HUBUNGAN DISLIPIDEMIA DAN DIABETES MELITUS TIPE 2 DITINJAU DARI KOLESTEROL & TRIGLISERIDA DI RSDI BANJARBARU - Rizka Ayu Wahyuni; Aulia Syafa Al Fitri; Nurbidayah Nurbidayah; Nurul Amalia; Noor Zahwa Mubarakah (Klinikal Sains : Jurnal Analis Kesehatan, 2026)
Type 2 Diabetes Mellitus is one of the non-communicable diseases with an increasing prevalence and a major contribution to cardiovascular complications. Insulin resistance in Type 2 Diabetes Mellitus not only causes hyperglycemia but may also affect lipid metabolism, potentially leading to dyslipidemia. This study aimed to determine the relationship between blood glucose levels and total cholesterol and triglyceride levels in patients with Type 2 Diabetes Mellitus. This research used an analytic design with a cross-sectional approach involving 45 patients with Type 2 Diabetes Mellitus who underwent lipid profile examination at the Clinical Pathology Laboratory of RSDI Banjarbaru. Data were analyzed using the Chi-Square test to assess the association between variables. The results showed that there was no significant relationship between blood glucose levels and total cholesterol levels or triglyceride levels (p > 0.05). Increased blood glucose levels were not statistically associated with elevated lipid levels in patients with Type 2 Diabetes Mellitus.